Developing inclusive practice: teacher perceptions of opportunities and constraints in the Republic of Ireland - FLYNN, PAULA; SHEVLIN, MICHAEL GERALD; WINTER, EILEEN (International Journal of Inclusive Education, 2013)
There has been a signi?cant policy shift from parallel systems of special and mainstream education in the Republic of Ireland towards provision underpinned by enabling legislation with a presumption for inclusion. The role of teachers in establishing inclusive learning environments is critical and it is generally accepted that inclusive practice relies to a large extent on teacher knowledge, skills, understanding, capacity and attitudes. This exploratory study aimed to gather information on teachers? attitudes about inclusion, and perceived constraints in creating inclusive learning environments. A range of schools from urban, semi-urban, provincial and rural backgrounds were included and data were collected using semi-structured interviews (n ? 24) including all principals, class teachers and support staff in the participating schools. Teachers recognised the challenge of responding appropriately to diversity within schools and are generally supportive of the principle of inclusion. However, there are clear concerns around their individual capacity and the capacity of their schools to develop inclusive learning environments. A positive school ethos was a signi?cant factor in ensuring inclusive practice. International research indicates that the complex mix of positive teacher beliefs combined with fears and perceived inadequacies is quite common in the evolution of practice towards inclusive learning environments
PUBLISHED
Keywords: : inclusive education; special education needs; teacher attitudes; school ethos; constraints